Nonparametric dynamical model of cardiorespiratory responses at the onset and offset of treadmill exercises - Hairong Yu; Lin Ye; Ganesh R. Naik; Rong Song; Hung T. Nguyen; Steven W. Su (Medical & Biological Engineering & Computing, 2018)

Patterns and drivers of species diversity in the Indo‐Pacific red seaweed Portieria - Frederik Leliaert; Dioli Ann Payo; Carlos Frederico D. Gurgel; Tom Schils; Stefano G. A. Draisma; Gary W. Saunders; Mitsunobu Kamiya; Alison R. Sherwood; Showe‐Mei Lin; John M. Huisman; Line Le Gall; Robert J. Anderson; et al. (Journal of Biogeography, 2018)
Aim Biogeographical processes underlying Indo‐Pacific biodiversity patterns have been relatively well studied in marine shallow water invertebrates and fishes, but have been explored much less extensively in seaweeds, despite these organisms often displaying markedly different patterns. Using the marine red alga Portieria as a model, we aim to gain understanding of the evolutionary processes generating seaweed biogeographical patterns. Our results will be evaluated and compared with known patterns and processes in animals. Location Indo‐Pacific marine region. Methods Species diversity estimates were inferred using DNA ‐based species delimitation methods. Historical biogeographical patterns were inferred based on a six‐gene time‐calibrated phylogeny, distribution data of 802 specimens, and probabilistic modelling of geographical range evolution. The importance of geographical isolation for speciation was further evaluated by population genetic analyses at the intraspecific level. Results We delimited 92 candidate species, most with restricted distributions, suggesting low dispersal capacity. Highest species diversity was found in the Indo‐Malay Archipelago ( IMA ). Our phylogeny indicates that Portieria originated during the late Cretaceous in the area that is now the Central Indo‐Pacific. The biogeographical history of Portieria includes repeated dispersal events to peripheral regions, followed by long‐term persistence and diversification of lineages within those regions, and limited dispersal back to the IMA . Main conclusions Our results suggest that the long geological history of the IMA played an important role in shaping Portieria diversity. High species richness in the IMA resulted from a combination of speciation at small spatial scales, possibly as a result of increased regional habitat diversity from the Eocene onwards, and species accumulation via dispersal and/or island integration through tectonic movement. Our results are consistent with the biodiversity feedback model, in which biodiversity hotspots act as both “centres of origin” and “centres of accumulation,” and corroborate previous findings for invertebrates and fish that there is no single unifying model explaining the biological diversity within the IMA .

Speciation in the mountains and dispersal by rivers: Molecular phylogeny of Eulamprus water skinks and the biogeography of Eastern Australia - Mitzy Pepper; Joanna Sumner; Ian G. Brennan; Kate Hodges; Alan R. Lemmon; Emily Moriarty Lemmon; Garry Peterson; Daniel L. Rabosky; Lin Schwarzkopf; Ian A. W. Scott; Glenn Shea; J. Scott Keogh (Journal of Biogeography, 2018)
Aim To develop a robust phylogeny for the iconic Australian water skinks ( Eulamprus ) and to explore the influence of landscape evolution of eastern Australia on phylogeographic patterns. Location Eastern and south‐eastern Australia. Methods We used Sanger methods to sequence a mitochondrial DNA (mt DNA ) locus for 386 individuals across the five Eulamprus species to elucidate phylogeographic structure. We also sequenced a second mt DNA locus and four nuclear DNA ( nDNA ) loci for a subset of individuals to help inform our sampling strategy for next‐generation sequencing. Finally, we generated an anchored hybrid enrichment ( AHE ) approach to sequence 378 loci for 25 individuals representing the major lineages identified in our Sanger dataset. These data were used to resolve the phylogenetic relationships among the species using coalescent‐based species tree inference in * BEAST and ASTRAL . Results The relationships between Eulamprus species were resolved with a high level of confidence using our AHE dataset. In addition, our extensive mt DNA sampling revealed substantial phylogeographic structure in all species, with the exception of the geographically highly restricted E . leuraensis . Ratios of patristic distances (mt DNA / nDNA ) indicate on average a 30‐fold greater distance as estimated using the mt DNA locus ND 4. Main conclusions The major divergences between lineages strongly support previously identified biogeographic barriers in eastern Australia based on studies of other taxa. These breaks appear to correlate with regions where the Great Escarpment is absent or obscure, suggesting topographic lowlands and the accompanying dry woodlands are a major barrier to dispersal for water skinks. While some river corridors, such as the Hunter Valley, were likely historically dry enough to inhibit the movement of Eulamprus populations, our data indicate that others, such as the Murray and Darling Rivers, are able to facilitate extensive gene flow through the vast arid and semi‐arid lowlands of New South Wales and South Australia. Comparing the patristic distances between the mitochondrial and AHE datasets highlights the continued value in analysing both types of data.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

DNA Barcoding for Identification of Sugarcane Borers in China - J- D Wang; W- Z Wang; Z- L Lin; A Ali; H- Y Fu; M- T Huang; S- J Gao; R Wang (Neotropical Entomology, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)